AB1011 LONG TERM FOLLOW-UP of THE PATIENTS WITH ANTI NUCLEAR ANTIBODY POSITIVITY WHO HAD INITIALLY NO IDENTIFIABLE RHEUMATIC DISEASES. (2nd June 2020) - Yildiz, M.; Altun, I.; Yilmaz, G.; Aliyeva, A.; Haslak, F.; Koker, O.; Adrovic, A.; Sahin, S.; Barut, K.; Kasapcopur, O.
Abstract : Background: Anti-nuclear antibodies (ANA) are a group of the antibodies that develop against intracellular components of the cells. It is usually useful for diagnosing some of the connective tissue diseases like systemic lupus erythematosus, mixed connective tissue disease. But it is reported that its positivity rate is about %20 in healthy individuals. Therefore, it can be confusing to check ANA test, if there is not really high suspicion for connective tissue diseases or juvenile idiopathic arthritis. Objectives: We aimed to evaluate results of long-term follow-up of the patients with ANA positivity who had initially no identifiable rheumatic diseases. Methods: Six hundred and ninety-four patients with ANA positivity who did not diagnosed as any of the rheumatic diseases at the first examination were found in database. Two hundred and eighty- two patients of them were called so far and questioned about their demographic features and symptoms that are related with rheumatic diseases. Results: Mean age of the patients at the time of study and at the time of testing were 13.4± 4.5 and 9.1±4.0 years. The female: male ratio was 1.05. Mean follow-up duration was 4.3±2.8 years. Most common reasons for the request for ANA test were arthralgia and skin eruptions. ANA testing was most commonly requested by a general pediatrists. Demographic features of the patients were summarized in Table 1 . Most of the diseases were diagnosed in patients with ANA positivity were not related with autoimmune mechanisms that associated with ANA positivity therefore, these diseases are thought to be coincidence. Only in 1 patients, systemic lupus erythematosus that has certain association with ANA positivity were diagnosed. All diseases that are diagnosed were shown in Table 2 . Conclusion: We are reporting that in only 0.3% of patients with ANA positivity who don't have any diseases diagnosed initially, were diagnosed as rheumatologic diseases during to the follow-up period. Since positivity of ANA is also common in the healthy population, requesting this test in only patients with high suspicion for connective tissue disease will reduce confusion in terms of diagnosis. References: [1]Kasapcopur O, Ozbakir F, Arisoy N, Ingol H, Yazici H, Ozdogan H. Frequency of antinuclear antibodies and rheumatoid factor in healthy Turkish children. Turk J Pediatr 1999;41:67-71. Disclosure of Interests: None declared